Description of The Collaboration of Nurses and Doctors Interprofession Communication - MJW, Endrian; Febriana, Reka; Setiawan, Henri (LPPM STIKes Muhammadiyah Ciamis, 2025)
Interprofessional Collaboration (IPC) is a collaboration between health professionals with different educational backgrounds into a collaborative team to improve the quality of effective services, communication inaccuracies in interprofessional collaboration have a serious impact on caring for patients, ineffective communication that occurs between nurses and doctors is the most important thing. mentioned as the cause in sentinel cases. This study aims to describe the collaboration interprofessional communication between nurses and doctors at Ciamis Hospital. Analytical research methodsdescriptive population with a total population of 407 nurses in the inpatient room of Ciamis Hospital and sampling using purposive sampling method with a population of 59 respondents, and using primary data obtained from the questionnaire sheet.The results showed that nurses had used the SBAR and TBAK communication methods, 39 respondents (66.1%) had effective communication with doctors, 20 respondents (33.9%) had ineffective communication between nurses and doctors. Conclusion Interprofessional Communication Collaboration between Nurses and Doctors at Ciamis Hospital has communicated effectively.